(untitled) - Leon, Wynne (Indianapolis, IN, 2007)
SharePoint Server 2007 offers incredible versatility to content managers, project managers, and administrators, and here's everything you need to know to harness its power. Create Office-compatible collaborative Web sites, corporate intranets and portals, document management systems, and much more. This essential reference helps you deploy, configure, customize, and troubleshoot SharePoint to maximize business intelligence, manage records and Web content, enable collaboration among employees and customers, and boost business success.
Keywords: Intranets (Computer networks),Microsoft SharePoint (Electronic resource),Web servers